6d+2d-6d-5=2d

Simple and best practice solution for 6d+2d-6d-5=2d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6d+2d-6d-5=2d equation:


Simplifying
6d + 2d + -6d + -5 = 2d

Reorder the terms:
-5 + 6d + 2d + -6d = 2d

Combine like terms: 6d + 2d = 8d
-5 + 8d + -6d = 2d

Combine like terms: 8d + -6d = 2d
-5 + 2d = 2d

Add '-2d' to each side of the equation.
-5 + 2d + -2d = 2d + -2d

Combine like terms: 2d + -2d = 0
-5 + 0 = 2d + -2d
-5 = 2d + -2d

Combine like terms: 2d + -2d = 0
-5 = 0

Solving
-5 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -0.6=1.4+x | | 2x+00=180 | | 20=0.55555556(F-32) | | 52.00=9.75t+3.25 | | 1.1y+0.3=-1.3-0.3y | | 7=x+3.4 | | x-4+3+x=74 | | 8x-3=9+7x | | x-4+3x=74 | | -2(4b+3)-10= | | 6*(4.5y-12)=9 | | 8x-3=9+7 | | x-4+x+3x=74 | | 3x^2+8=251 | | m+m+2m-15= | | 8x=30-7x | | x-9=3.7 | | 3.80=15.20 | | 3x+4=7x-3 | | 7(a-4)+8= | | 1-8x=-39 | | -7-3(4a-8)=-3a-2(-2-2a) | | 16s^2=64 | | 9pq-9p+13pq= | | (y+9)(2y-3)= | | x-2.7=2.5 | | 4n-(6)=10n | | 3x^2-3-246=0 | | 6(2a+10)=5(2+5) | | 32-2(10-4)=45x | | 7*2-1(6*2-5)=7 | | 0.4x-0.2(3-x)=14 |

Equations solver categories